The Gannon Storm: citizen science observations during the geomagnetic superstorm of 10 May 2024 - Grandin, Maxime; Bruus, Emma; Ledvina, Vincent E.; Partamies, Noora; Barthelemy, Mathieu; Martinis, Carlos; Dayton-Oxland, Rowan; Gallardo-Lacourt, Bea; Nishimura, Yukitoshi; Herlingshaw, Katie; Thomas, Neethal; Karvinen, Eero; et al. (Copernicus Publications, 2025)
The 10 May 2024 geomagnetic storm, referred to as the Gannon Storm in this paper, was one of the most extreme to have occurred in over 20 years. In the era of smartphones and social media, millions of people from all around the world were alerted to the possibility of exceptional auroral displays. Hence, many people not only witnessed but also photographed the aurora during this event. These citizen science observations, although not from scientific instruments operated by observatories or research groups, can prove to be invaluable in obtaining data to characterise this extraordinary event. In particular, many observers saw and photographed the aurora at mid-latitudes, where ground-based instruments targeting auroral studies are sparse or absent. Moreover, the proximity of the event to the Northern Hemisphere summer solstice meant that many optical instruments were not in operation due to the lack of suitably dark conditions. We created an online survey and circulated it within networks of aurora photographers to collect observations of the aurora and of disruptions in technological systems that were experienced during this superstorm. We obtained 696 citizen science reports from over 30 countries, containing information such as the time and location of aurora sightings and the observed colours and auroral forms, as well as geolocalisation, network, and power disruptions noticed during the geomagnetic storm. We supplemented the obtained dataset with 186 auroral observations logged in the Skywarden catalogue (https://taivaanvahti.fi, last access: 19 December 2024) by citizen scientists. The main findings enabled by the data collected through these reports are that the aurora was widely seen from locations at geomagnetic latitudes ranging between 30 and 60°, with a few reports from even lower latitudes. This was significantly further equatorward than predicted by auroral oval models. The reported auroral emission colours, predominantly red and pink and intense enough to reach naked-eye visibility, suggest that ...